5G SA converged charging project design and practice - Dongfeng MAO; Song JIANG; Qing WANG (Dianxin kexue)
There are some challenges of direct communication and converged charging in large SA network construction to be solved.A converged charging project based on SCP and customized CG was proposed, following by analysis of how to meet converged charging requirements of large operators.Technology details of several cases and presents target evolution were compared.Finally, the deployment practice in commercial construction was described.